2016
DOI: 10.1007/s10802-016-0164-6
|View full text |Cite
|
Sign up to set email alerts
|

The Multivariate Roles of Family Instability and Interparental Conflict in Predicting Children’s Representations of Insecurity in the Family System and Early School Adjustment Problems

Abstract: This study examined the moderating role of family instability in relations involving destructive interparental conflict, children’s internal representations of insecurity in the family system, and their early school maladjustment. Two hundred forty-three preschool children (M age = 4.60 years; 56% girls) and their families participated in this multi-method (i.e., observations, structured interview, surveys) multi-informant (i.e., observer, parent, teacher), longitudinal study. Findings indicated that the media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 47 publications
1
25
0
7
Order By: Relevance
“…En cuanto a las limitaciones del presente estudio, es preciso señalar que no se ofrece evidencia acerca de su validez externa, tanto convergente, con instrumentos de medida que evalúen constructos similares, como discriminante, con instrumentos que midan constructos hipotéticamente relacionados con la actitud parental ante el conflicto. Futuras líneas de investigación pueden centrarse en analizar cómo la actitud parental percibida ante un conflicto se relaciona con variables relacionadas como los estilos de crianza (Smetana, 2017), de apego (Jones, Cassidy, y Shaver, 2015) o el funcionamiento familiar en presencia de conflicto (Coe, Davies, y Sturge-Apple, 2017).…”
Section: Discussionunclassified
“…En cuanto a las limitaciones del presente estudio, es preciso señalar que no se ofrece evidencia acerca de su validez externa, tanto convergente, con instrumentos de medida que evalúen constructos similares, como discriminante, con instrumentos que midan constructos hipotéticamente relacionados con la actitud parental ante el conflicto. Futuras líneas de investigación pueden centrarse en analizar cómo la actitud parental percibida ante un conflicto se relaciona con variables relacionadas como los estilos de crianza (Smetana, 2017), de apego (Jones, Cassidy, y Shaver, 2015) o el funcionamiento familiar en presencia de conflicto (Coe, Davies, y Sturge-Apple, 2017).…”
Section: Discussionunclassified
“…However, the EST posits that despite the short-term usefulness of the disengagement and preoccupation strategies, the psychological and physical resources used to maintain security reduce the resources available to other processes that are needed for development. Thus, as numerous longitudinal and cross-sectional studies have shown, children using such strategies are at increased risk of developing difficulties such as eating disorders [25], symptoms of hyperactivity [26], adaptation problems in school [27], or addictions [28]. Although numerous studies have tested the EST in the general population, to date, only one work has analyzed the relationship between emotional security/insecurity in the emotional system and mental health of CSA victims [29].…”
Section: Emotional Security In the Family Systemmentioning
confidence: 99%
“…Numerosos estudios han analizado el impacto de la seguridad emocional en el sistema familiar sobre el bienestar psicológico de los menores (Bi, Haak, G ilbert y Keller, 2017;Cantón-Cortés et al, 2016;Cantón-Cortés, Cortés y Cantón, 2019;Coe, Davies y Sturge-Apple, 2017;Zhou et al, 2017). Zhou et al, (2017), por ejemplo, encontraron en una muestra de 1.189 adolescentes que la inseguridad emocional se relacionaba con la adicción a internet.…”
Section: Seguridad Emocional En El Sistema Familiarunclassified